Od Bilbao efektu ku High Line efektu - Krištof, Michal (Vysoké učení technické v Brně, Fakulta architektury, 2014)
In last 50 years it is possible to trace changing role of architecture in urban development strategies. Two main tendencies is possible to identify. Fisrt strategy is a realisation of an iconic building as a flagship of new development of the city. The most obvious example of this approach is Guggenheim Museum in Bilbao. Second strategy evidents in last decade is usage of public space as a catalist of continuous transformation and development of cities. The best example could be High Line in New York.
Keywords: sustainability; public space; city; economy; High Line; Guggenheim Museum; Bilbao effect; New York; Manchester; Irwell City Park